1996
DOI: 10.1177/082957359601100220
|View full text |Cite
|
Sign up to set email alerts
|

Bully and Victim Problems in Elementary Schools and Students' Beliefs about Aggression

Abstract: The study was undertaken to survey the prevalence and nature of bullying in elementary school children; and to investigate the bullies and victims' beliefs supporting aggression. A total of 379 grades 4 to 6 students in Calgary were surveyed. Results of the Bully/Victim Questionnaire (Olweus, 1989) indicated that 21.3% were bullied and 11.6% bullied others "sometimes" or more often at school that term. Victims tended to be the youngest students of the sample, both boys and girls, and were at risk for being bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
55
3
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 15 publications
13
55
3
8
Order By: Relevance
“…This could be a tangible reward, enhancement of self-esteem or status, peer admiration, etc. Bullies are more likely than their non aggressive peers to legitimize aggression and expect a positive outcome from bullying (Bentley & Li, 1995;Crick & Dodge, 1996;Deluty, 1983;Dodge et al, 1986 (2004) found that physical bullying was a significant predictor of Internet bullying, but examined only limited forms of t-bullying and c-bullying (e.g. mobile phone use was not included).…”
mentioning
confidence: 99%
“…This could be a tangible reward, enhancement of self-esteem or status, peer admiration, etc. Bullies are more likely than their non aggressive peers to legitimize aggression and expect a positive outcome from bullying (Bentley & Li, 1995;Crick & Dodge, 1996;Deluty, 1983;Dodge et al, 1986 (2004) found that physical bullying was a significant predictor of Internet bullying, but examined only limited forms of t-bullying and c-bullying (e.g. mobile phone use was not included).…”
mentioning
confidence: 99%
“…Respecto a las actitudes mejoradas se apoya el hecho de ser percibido como diferente o en situación de debilidad, incrementa considerablemente el riesgo de ser víctima de la violencia (Diaz-Aguado, 2007), así como la relación entre las creencias que justifican la violencia y su utilización, siendo los agresores quienes manifiestan un superior acuerdo con dichas creencias (Bentley y Li, 1995;Bosworth et al, 1999). También ocurre en la relación existente entre el bullying, el sexismo y la violencia de género (Connolly et al, 2000).…”
Section: Conclusionesunclassified
“…Estudos comprovam que autores de bullying estão mais propensos ao uso de drogas, álcool e transtornos psiquiá-tricos (FEKKES;PIJPERS;VERLOOVE-VANHORICK, 2005) e que têm grandes difi culdades de se adaptar à escola e de obedecer às regras -fato que denota a possibilidade de agirem mal como única alternativa ou legítima resposta para se verem livres de problemas nas relações sociais com os pares (OLWEUS, 1997;BENTLEY;LI, 1995;BOSWORTH;ESPELAGE;SIMON, 1999), haja vista as poucas habilidades sociais que têm (AVILÉS, 2006). São esses que mais precisam ser o centro das atenções, o que talvez seja um modo de esconder o medo de não serem aceitos.…”
Section: O Fenômeno Bullyingunclassified